EFFECT OF NUMBER OF TRANSITION METAL CATALYST CELLS MANGANESE CATALYTIC CONVERTER ON EXHAUST BASIS EMISSION OUTPUT CARBON MONOXIDE MOTOR GASOLINE - Irawan, RM. Bagus; Pujianto, Edi; Amin, Moh; Subri, Moh (Universitas Muhammadiyah Jakarta, 2021)
The technology used to reduce air pollution is using a Catalytic Converter which is installed on the exhaust gas channel (muffler) of gasoline motorized vehicles. This Catalytic Converter serves to accelerate the oxidation of Hydrocarbon (HC) and Carbon Monoxide (CO) emissions, as well as to reduce Nitrogen Oxide (NOx). In this study it was designed in such a way on a laboratory scale by studying the manganese transition metal material as a supporting copper catalyst, to see the ability of the catalyst to reduce carbon monoxide exhaust emissions. This study aims first to examine the ability of the manganese transition metal catalyst as a support for copper (CuMn) and secondly to examine the effect of increasing the number of catalyst cells on exhaust emission output. The first research results obtained were that the Manganese Transition metal catalyst as a supporting Copper (CuMn) was able to reduce the output of Carbon Monoxide exhaust emissions. Second, the addition of the number of catalyst cells on the Copper (Cu) catalyst did not have a significant effect, while the addition of the number of catalyst cells on the Manganese Transition metal catalyst as a support for Copper, from 5 catalysts to 10 catalysts, was able to reduce the output of Carbon Monoxide exhaust gas more significantly. However, in the number of 15 catalyst cells, the reduction in exhaust emissions was not significant.